The Cost of Being Under the Weather: Droughts, Floods, and Health Care Costs in Sri Lanka - Diana De Alwis; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2017)
We measure to cost of extreme weather events (droughts and floods) on health care in Sri Lanka. We find that frequently occurring local floods and droughts impose a significant risk to health when individuals are exposed directly to these hazards, and when their communities are exposed, even if they themselves are unaffected. Those impacts, and especially the indirect spillover effects to households that are not directly affected, are associated with the land-use in the affected regions and with access to sanitation and hygiene. Finally, both direct and indirect risks associated with flood and drought on health have an economic cost; our estimates suggest Sri Lanka spends 52.8 million USD per year directly on the health care costs associated with floods and droughts, divided almost equally between the public and household sectors, and 22% vs. 78% between floods and droughts, respectively. In Sri Lanka, both the frequency and the intensity of droughts and floods are likely to increase because of climatic change. Consequently, the health burden associated with these events is only likely to increase, demanding precious resources that are required elsewhere.
Keywords: I15; Q54; 330; Sri Lanka; flood; drought; health impact